Perbedaan efektivitas obat kumur yang mengandung chlorhexidine dan essential oils terhadap penurunan tingkat halitosis - Arum Dyah Pangesti; Desak Nym Ari Susanti; Sari Kusumadewi (Bali Dental Journal, 2018)
Background: Halitosis is a malodor comes from the oral cavity and it is quite serious problem that can cause low self-esteem to a person. Main cause of halitosis is the release of volatile sulphur compounds (VSCs) produced by anaerobic bacterial activity inside the oral cavity. One of the ways to overcome halitosis is using mouthwash. Available mouthwashes in market are chlorhexidine and essential oil. Chlorhexidine is a broad-spectrum antimicrobial drug. Its roles are as an antiseptic agent, an effective bactericidal agent against all kinds of microbe, including bacteria, yeast, and virus. An essential oils mouthwash has antimicrobial effect and prevents bacterial aggregation. Its mechanisms through bacterial cell destruction, bacterial enzyme inhibition and endotoxin extraction from Gram negative bacteria that can cause halitosis. Objective: This study aimed to know comparison effectivity between chlorhexidine and essential oil contained in mouthwash in decreases of halitosis level. Methods: Experimental method is used in this study, comprised 32 subject divided into 2 group who had criteria for inclusion. Group 1 rinsed using chlorhexidine mouthwash and group 2 rinsed using essential oils mouthwash. The measurement was done before intervention, first 20 minutes, 40 minutes and 60 minutes. Results: Collected data was analyzed using Shapiro Wilk for normality test and non parametric Mann-Whitney for statistical hypothesis test. Result There was different effectiveness of chlorhexidine and essential oils mouthwashes in reducing halitosis level. Conclusion: Chlorhexidine is more effective in reducing halitosis compared to essential oils.